Behind the scenes of the New Testament: cultural, social, and historical contexts - Longenecker, Bruce W.; Shively, Elizabeth E.; Lang, T. J. (Baker Academic, 2024)
A team of world-class scholars covers the full range of New Testament backgrounds studies in a concise, authoritative, and comprehensive manner.